WOLVERINE DATA - Milleret, Cyril; Dupont, Pierre; Brøseth, Henrik; Kindberg, Jonas; Royle, J; Bischof, Richard (Dryad Digital Repository, 2018)
The "WOLVERINE.Rdata" file contains the Rdata necessary to run the wolverines males and females empirical example at the original grid cell size (2*2kms) with a Bernoulli model. The README.R file contains the R script and data description necessary to run the JAGS models.